Identification of the bchP Gene, Encoding Geranylgeranyl Reductase in Chlorobaculum tepidum - Gomez Maqueo Chew, Aline (American Society for Microbiology (ASM), 2008)
The Chlorobaculum tepidum genome contains two paralogous genes, CT2256 and CT1232, whose products are members of the FixC dehydrogenase superfamily and have sequence similarity to geranylgeranyl reductases. Each gene was insertionally inactivated, and the resulting mutants were characterized. CT2256 encodes geranylgeranyl reductase (BchP); CT1232 is not involved in bacteriochlorophyll or chlorophyll biosynthesis.